Genesis of social security regulation for police officers in Ukraine - A. S. Kolotik (Bulletin of Kharkiv National University of Internal Affairs)
The police reform launched in Ukraine in 2015 was a very important and long-overdue step towards the transformation of both the system of the Ministry of Internal Affairs of Ukraine and the law enforcement system of the country as a whole. However, today, more than seven years after the adoption of the Law of Ukraine “On the National Police”, the reform is still not fully completed, and sharp criticism of numerous problems and shortcomings in the reform process is often heard in the academic community and among representatives of the practical sphere of law. We do not deny the existence of certain gaps and other problematic issues in the current legal framework for the organisation and functioning of the police in Ukraine, but we do not agree with the current opinion that the police reform has failed. A number of aspects, including the state of legislative regulation of social security for police officers, demonstrate the necessary and important positive developments and changes in this area. In order to prove this position, an analysis of the genesis of legal regulation of social security for police officers is made in the article, which will allow tracing the changes in this area both during the period when our State was a part of the Soviet empire and after the declaration of independence and introduction of new ideas and principles of development of the Ukrainian statehood.